Os condomínios horizontais fechados e as transformações socioespaciais na cidade de Natal/RN - Tavares, Matheus Augusto Avelino (2009)
The process of urbanization of Natal city has been going in the last years by importants changes, mainly, because we can observe the development of a new kind of housing: the horizontal closed condominiums, from 1995 began to expand quickly on the city. In this way, the present study has as objective analyse the expansion of the horizontal closed condominiums on the urban area of Natal. Emphasizing the sociogeographic changes that these ventures engender. For this, we have done a research that was based on quantitative procedures, however, preferring a qualitative approach. So, data were gathered from sources and procedures: the first, we performed a literature search and document on issues related to the relevant issues in libraries, public and privates institutions; The second, in accordance with the procedures, or the production of informations, performed enterview and implemetation of questionnaires with key stakeholders involved with the expansion of horizontal condominiums in Natal. Within this perspective, our research showed that the expansion of demand in the city, the existence of volume of land in areas suitable for the production building, the formation of capital property, the appearance of new points of modern consumption, the actions of the state and the low cost of production of these enterprises, are factors that have been decisive in the expansion of the horizontal condominiums in Natal. Also, we can observe that the process of production of the urban space from the horizontal condominiums comes in providing the redefinition of land use in areas that appear, because they expand into outlying areas of Natal, changes in its structure and its pattern of socio segregation, observing that the condominiums put the diferents social groups living side by side, but not mantaining relationships among them, the emergence of spaces to homogenization, the fragmentation of the urbanization, the privatization of the city and several environmental problems. In short, we believe that the horizontal expansion of condominiums is enabling a number of social changes to Natal city